For a Powerful Geography in the Brazilian National Curriculum - Castellar, Sonia Maria Vanzella; Pereira, Carolina Machado Rocha Busch; Guimarães, Raul Borges [UNESP] (Springer Nature, 2021)
This chapter presents an overview of the elaboration of the Brazilian Common Core Curriculum (BNCC), that is, the national school curriculum, in the specific context of Geography teaching, for which the BNCC is both the national reference and the methodological framework. The process of the consolidation of the primary, elementary and secondary school curricula is presented, and the implementation of these curricula by the different Brazilian states and municipalities is also discussed. The chapter is organised in three sections: (i) the historical context of educational policies in Brazil, including its political implications and organisational boundaries, (ii) geographical reasoning based on real situations, and (iii) the role of Geography in the Brazilian Common Core Curriculum.
Keywords: Curriculum; Education; Geographical reasoning; Geography